The eternal quest for self-improvement of somatic cells - Peter J. Campbell (Elsevier, 2022)
Summary: Multiple somatic mutations drive cancer cell transformation, but the sequence of events is poorly understood. In this issue of Cell Genomics, Kester et al. combine organoid technology, prospective barcode labeling, and single-cell sequencing to study the evolution of somatic clones in vitro.